Answer:
223.56$
The ans is simple
Add all the given values
Then we get the ans
Step-by-step explanation:
The ans is simple
Add all the given values
Then we get the ans
Answer:
P = - 8
Step-by-step explanation:
Given
P = x + y ← substitute x = - 5 and y = - 3
P = - 5 + (- 3) = - 5 - 3 = - 8
Answer:
the equation is : x²-x-12
Step-by-step explanation:
the quadratic equation is in the form of : y=ax²+bx+c
the product of the zeros is -12 and the sum is 1
b = - 1
c=-12 (product)
y=x²-x-12
check : factorize first (x+3)(x-4)=0
either x+3=0 then x=-3
or x-4=0 then x=4
-3*4=-12
-3+4=1
the equation is : x²-x-12
<span>Since Jeff is paying an annual amount of $744 he needs to set aside 12 monthly payments for the year. To figure out how much each payment would be you divide the total for the year 744 by the number of months 12. $744/12=$62 Each monthly payment would be $62</span>
Answer:
The required product is
Step-by-step explanation:
Consider the provided expression.
Open the parentheses.
Add the like terms.
Hence, the required product is